2016
DOI: 10.1193/010816eqs007ep
|View full text |Cite
|
Sign up to set email alerts
|

Loading Protocols for ASCE 41 Backbone Curves

Abstract: ASCE 41 is the industry standard for seismic evaluation and retrofit of existing buildings. It allows for alternative component modeling and acceptance criteria based on a backbone curve constructed from envelopes of component hysteresis loops derived via experimental cyclic tests. ASCE 41-13 requires use of loading protocols having fully reversed cyclic loadings with increasing displacement levels. However, recent research summarized herein indicates the need for inclusion of different protocols that pay spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 4 publications
2
35
0
1
Order By: Relevance
“…A DE-level protocol corresponding to a design earthquake (DE) is similar to the MCE-level protocol except with several more major excursions at smaller peak drift. Even response from long duration great earthquakes has a similar pattern except with more excursions (Maison and Speicher 2018).…”
Section: Effect Of Loading Protocolsmentioning
confidence: 91%
See 1 more Smart Citation
“…A DE-level protocol corresponding to a design earthquake (DE) is similar to the MCE-level protocol except with several more major excursions at smaller peak drift. Even response from long duration great earthquakes has a similar pattern except with more excursions (Maison and Speicher 2018).…”
Section: Effect Of Loading Protocolsmentioning
confidence: 91%
“…2(a). Standard protocols can be too demanding, leading to conservative estimates of deformation capacity (Maison and Speicher 2016). Fig.…”
Section: Effect Of Loading Protocolsmentioning
confidence: 99%
“…Noteworthy stating that for Specimen A3, which was subjected to a collapse-consistent lateral loading history, the predicted θpc value was well correlated with the measured one. This suggests the need for more refined lateral loading protocols for component modeling and acceptance criteria of structural components (Suzuki and Lignos 2014;Maison and Speicher 2016).…”
Section: Elastic Effective Stiffness Kementioning
confidence: 99%
“…Therefore, their applicability to the nonlinear modeling of steel columns shall be carefully examined since PEER/ATC (2010) modeling guidelines neglect important loading (e.g., axial load) and geometric parameters (e.g., Lb/ry) that may significantly affect the column behavior under cyclic loading. The need for more monotonic test data in addition to the ones based on reversed cyclic loading is also apparent (Haselton et al 2008;Krawinkler 2009;Maison and Speicher 2016). The reason is that a monotonic backbone curve, which is considered as a unique property of a structural component, is typically used to benchmark models that explicitly capture component cyclic deterioration in strength and stiffness for use in nonlinear dynamic analysis (Lignos and Krawinkler 2011;Hamburger et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, in line with AISC358-16 [3], the loading protocols adopted to qualify/test beam-to-column joints within EQUALJOINTS project were representative of the cumulative and maximum rotation demands imposed by far-field natural records [10,11]. A recent study [12] has indicated that such protocols are not representative of the actual seismic demands at near-collapse conditions. Indeed, under that limit state, the earthquakes induce relatively few large displacement excursions in one direction.…”
Section: Introductionmentioning
confidence: 99%